Novel Long Non-coding RNA Expression Profile of Peripheral Blood Mononuclear Cells Reveals Potential Biomarkers and Regulatory Mechanisms in Systemic Lupus Erythematosus - Cheng, Qi; Chen, Mo; Chen, Xin; Chen, Xiaochan; Jiang, Huawei; Wu, Huaxiang; Du, Yan (Frontiers in Cell and Developmental Biology, 2021)
Objective The multisystem involvement and high heterogeneity of systemic lupus erythematosus (SLE) lead to great challenges in its diagnosis and treatment. The purpose of this study was to find new lncRNAs in peripheral blood mononuclear cells of SLE patients by transcriptome sequencing and explore their potential as biomarkers and their correlation with clinical features. Materials and Methods Transcriptome sequencing was used to screen differentially expressed lncRNAs (DELs) and mRNAs (DEMs). The expression of these selected lncRNAs and mRNAs in SLE patients and healthy controls was verified by qPCR. DAVID and WebGestalt were used to perform enrichment analysis. Cytoscape was used to construct a protein–protein network, a coexpression network, and a competitive endogenous RNA network to reveal the regulatory mechanisms of lncRNAs at the transcriptome level. Results A total of 1737 DELs and 4078 DEMs were identified between SLE patients and healthy controls. Ten lncRNAs and eight genes were verified by qPCR in a larger sample set. The lncRNA NONHSAT101022.2 was significantly downregulated in SLE patients and was also significantly related to the activity and severity of disease. The upregulated genes were enriched in defense and the immune response, while the downregulated genes were mainly enriched in SLE-related pathways. Topology network analysis revealed that the lncRNAs were involved in regulation at the transcriptome level, including acting directly on mRNA or indirectly affecting gene expression by acting on miRNA. Conclusion In this work, we identified many mRNAs and novel lncRNAs by transcriptome sequencing. The functions and regulatory mechanisms of these lncRNAs were analyzed by bioinformatic methods. The novel lncRNA NONHSAT101022.2 is significantly downregulated in SLE patients and is significantly related to the activity and severity of disease. Additionally, we propose that NONHSAT101022.2 may enhance the signal transduction of β2-AR by cis regulating LMBRD2, inducing NK cells to produce high levels of IFN-γ and thereby exacerbating SLE.